2018
DOI: 10.5194/hess-22-4061-2018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding terrestrial water storage variations in northern latitudes across scales

Abstract: Abstract. The GRACE satellites provide signals of total terrestrial water storage (TWS) variations over large spatial domains at seasonal to inter-annual timescales. While the GRACE data have been extensively and successfully used to assess spatio-temporal changes in TWS, little effort has been made to quantify the relative contributions of snowpacks, soil moisture, and other components to the integrated TWS signal across northern latitudes, which is essential to gain a better insight into the underlying hydro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 89 publications
(116 reference statements)
9
37
0
Order By: Relevance
“…Our findings agree with the results of Trautmann et al (), who compared modeled TWS with GRACE TWS observation in mid‐ to high latitudes. They found that snow mass variations are the main contributor to seasonal TWS variation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings agree with the results of Trautmann et al (), who compared modeled TWS with GRACE TWS observation in mid‐ to high latitudes. They found that snow mass variations are the main contributor to seasonal TWS variation.…”
Section: Discussionsupporting
confidence: 92%
“…Although the GIA model might not effectively remove the contribution of this background signal from GRACE observations, the inconsistent behaviour of GRACE TWS variabilities, compared with multisource SWEA data, might not only be associated with linear trends. It is worth mentioning that the inter‐annual variations of GRACE TWS in the areas surrounding Hudson Bay are more uncertain and exhibit considerable noises that influence the information content of the observations (Humphrey et al, ; Trautmann et al, ). There might be other factors that influence the correlation results, such as de‐aliasing model (tides are poorly modeled over Hudson Bay) in Arctic coastal regions in Canada and the west coast of Hudson Bay (Humphrey et al, ; Rangelova et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, a very recent implementation of lateral flow in a global-scale LSM (Zeng et al, 2018), at a resolution similar to this study, shows similar bias with shallower WTD compared to that from Fan et al (2013). These discrepancies in global WTD estimates also suggests a need for better treatment of other global data sets, such as the Gravity Recovery and Climate Experiment terrestrial water storage variations (Tapley et al, 2004), in constraining global-scale model simulations of soil moisture-GW dynamics, as demonstrated previously in regional-scale studies (Lo et al, 2008;Trautmann et al, 2018).…”
Section: Summary Discussion and Limitationssupporting
confidence: 82%